HUBUNGAN ANTARA TIPE KENDARAAN DAN OBESITAS DENGAN RISIKO MUSCULOSKELETAL DISORDERS (MSDs) PADA MAHASISWA PENGENDARA SEPEDA MOTOR DI UNIVERSITAS UDAYANA - Gunawan, I Made Kasmadi; Tirtayasa, Ketut (E-Jurnal Medika Udayana, 2015)
CORRELATION BETWEEN TYPE OF VEHICLE AND OBESITY WITH RISK MUSCULOSKELETAL DISORDERS (MSDs) ON STUDENTS MOTORCYCLISTS IN UDAYANA UNIVERSITY Driving a motorcycle has some risks of a variety of disorders, particularly musculoskeletal disorders (MSDs). Musculoskeletal disorders motorcyclists vary, depending on factors in each individual because multifactorial nature of this disorder. One of these, types of vehicles and obesity. The aim of this study was to determine the relationship between the type of vehicle and obesity with musculoskeletal disorders, prevalence and distribution of musculoskeletal disorders. This study was conducted using cross sectional analytical method in motorcyclists among Udayana University students with a sample size of 50 people. Respondentsfill out questionnaires Nordic Body Map and measured body mass index. The result showed an increased risk of musculoskeletal disorders based Nordic Body Map of each group of vehicle types and also of analytic Chi-square test p value significant is 0,00 (p <0.05), Spearman correlation test showed a correlation with correlation value 0.661. An increased risk of musculoskeletal disorders based Nordic Body Map of each group of criteria for obesity and also of analytic Chi-square test p valuesignificant is 0.044 (p <0.05), Spearman correlation test showed a correlation with the correlation value 0.337.Distribution of musculoskeletal disorders found most complaint areas is on the neck, back, upper waist, lower back, and buttocks. It was concluded that the type of vehicle has a relationship with musculoskeletal disorders. Motor sport at greater risk of suffering from disorders musculoskeletal then followed by motor step-through, and matic. Furthermore, obesity has a correlation with musculoskeletal disorders. In people with obesity are more at risk to suffer musculoskeletal disorders.
Keywords: Obesity; type of vehicle; musculoskeletal disorders; Nordic Body Map